2016
DOI: 10.1080/17435390.2016.1206148
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanoparticles and organic chemical UV-filters are equally well tolerated by human immune cells

Abstract: An important part of assessing the toxic potential of nanoparticles for specific applications should be the direct comparison of biological activities with those of alternative materials for the same application. Nanoparticulate inorganic ultraviolet (UV) filters, such as zinc oxide (ZnO), are commonly incorporated into transparent sunscreen and cosmetic formulations. However, concerns have been raised about potential unwanted effects, despite their negligible skin penetration and inherent advantages over orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…They found that despite having a hydrophobic silane surface-coating (Singh et al, 2011), the coated ZnO nanoparticles behaved in a similar manner to the uncoated pristine ZnO regarding their lack of skin penetrance and toxicity and the slight elevation in zinc ion levels in the viable epidermis (Mohammed et al, 2018). This provides further confirmation that the range of ZnO nanoparticles used in sunscreen formulations do not penetrate human skin with realistic use conditions; thus, they have much lower skin penetrance than alternative materials used for the same application, such as organic chemical UV filters, which have similar direct in vitro cytotoxicity profiles (O'Keefe et al, 2016).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…They found that despite having a hydrophobic silane surface-coating (Singh et al, 2011), the coated ZnO nanoparticles behaved in a similar manner to the uncoated pristine ZnO regarding their lack of skin penetrance and toxicity and the slight elevation in zinc ion levels in the viable epidermis (Mohammed et al, 2018). This provides further confirmation that the range of ZnO nanoparticles used in sunscreen formulations do not penetrate human skin with realistic use conditions; thus, they have much lower skin penetrance than alternative materials used for the same application, such as organic chemical UV filters, which have similar direct in vitro cytotoxicity profiles (O'Keefe et al, 2016).…”
mentioning
confidence: 65%
“…The lack of toxicity from ZnO exposure seen in the new study is not surprising, because zinc is an essential mineral for human nutrition, and its transport and use are strictly controlled within the biological processes of the body. Cytotoxic responses from ZnO nanoparticles are seen at relatively high-exposure concentrations (Feltis et al, 2012), which are at least a magnitude greater than those expected from nanosunscreen use (O'Keefe et al, 2016), even in the case of human phagocytic immune cells that can actively concentrate ZnO nanoparticles . Mechanistic studies clearly indicate that ZnO's cytotoxicity is directly dependent on the extent of cellular uptake of nanoparticles, followed by their intracellular dissolution to zinc ions , and is not dependent on extracellular zinc release (Shen et al, 2013).…”
mentioning
confidence: 95%
“…Based on the results of MTT and LDH assays, it can be expressed as HMS having cytotoxic effect. O'Keefe et al demonstrated cytotoxic effects of organic and Zn nanoparticles five organic UV filters (including HMS) in human THP‐1 monocyte cells and macrophage cultures after 24 hours incubation. They found that the most cytotoxic organic UV filter was 4‐methylbenzylidene camphor, followed by HMS in monocytes and macrophages cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Although the daily use of UV filters are low, long‐term exposure to UV filters can cause cytotoxic and genotoxic effects . Reviewing the literature on the toxicological profile of HMS as a cosmetic ingredient, very few studies were found regarding the cytotoxic and genotoxic effects of HMS …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation